Analysis of gene mutation of early onset epileptic spasm with unknown reason - Yang, X (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2017)
Objective: To summarize the gene mutation of early onset epileptic spasm with unknown reason. Method: In this prospective study, data of patients with early onset epileptic spasm with unknown reason were collected from neurological department of Children's Hospital of Fudan University between March 2016 and December 2016. Patients with known disorders such as infection, metabolic, structural, immunological problems and known genetic mutations were excluded. Patients with genetic disease that can be diagnosed by clinical manifestations and phenotypic characteristics were also excluded. Genetic research methods included nervous system panel containing 1 427 epilepsy genes, whole exome sequencing (WES), analysis of copy number variation (CNV) and karyotype analysis of chromosome. The basic information, phenotypes, genetic results and the antiepileptic treatment of patients were analyzed. Result: Nine of the 17 cases with early onset epileptic spasm were boys and eight were girls. Patients' age at first seizure onset ranged from 1 day after birth to 8 months (median age of 3 months). The first hospital visit age ranged from 1 month to 2 years (median age of 4.5 months). The time of following-up ranged from 8 months to 3 years and 10 months. All the 17 patients had early onset epileptic spasm. Video electroencephalogram was used to monitor the spasm seizure. Five patients had Ohtahara syndrome, 10 had West syndrome, two had unclear classification. In 17 cases, 10 of them had detected pathogenic genes. Nine cases had point mutations, involving SCN2A, ARX, UNC80, KCNQ2, and GABRB3. Except one case of mutations in GABRB3 gene have been reported, all the other cases had new mutations. One patient had deletion mutation in CDKL5 gene. One CNV case had 6q 22.31 5.5MB repeats. Ten cases out of 17 were using 2-3 antiepileptic drugs (AEDs) and the drugs had no effect. Seven cases used adrenocorticotropic hormone (ACTH) and prednisone besides AEDs (a total course for 8 weeks). Among them, five cases had no effect and two cases were seizure free recently. A case with GABRB3 (C.905A>G) had seizure controlled for 3 mouths. A case with ARX (C.700G>A) had seizure controlled for 6 mouths. Conclusion: The early onset epileptic spasm with unknown reason is highly related to genetic disorders. A variety of genetic mutations, especially new mutations were found. Genetic heterogeneity of epileptic spasm is obvious